PENGARUH DISIPLIN DAN PENGAWASAN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI NEGERI SIPIL PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN NGANJUK - Istan Wighara Moelyono (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2017)
Human is an important element in an organization / company. To improve the maximum work for the agency. One of the most important factors in its role in determining success and achieving maximum results is labor. The labor factor is a human resource that has reason and mind, therefore it is not easy to coordinate it. So the discipline of work and work supervision and work effectiveness is a very important role in the process of completion of work.Problems taken in this research is the influence between discipline and supervision of work on the effectiveness of work and how much influence the discipline of work and supervision of work on the effectiveness of employment at the Regional Personnel Agency Nganjuk. The purpose of this study is to determine whether there is influence between work discipline and work supervision on the effectiveness of work and to find out how much influence the discipline of work and supervision of work against the Regional Personnel Agency Nganjuk.Population in this research is employee of Nganjuk Regency Government with sample officer of Badan Kepegawaian Daearah Nganjuk. Data collection tool in this research is questionnaire. The data collected were analyzed by descriptive percentage technique and multiple linear analysis using SPSS statistic program.The results showed that there is a significant influence simultaneously and partially between the discipline and supervision of work on the effectiveness of employees at the Regional Personnel Agency Nganjuk, This can be known from Fcount> Ftable (18,971> 2,45) while discipline t count <ttable (0,940 <2,021) and supervision tcount> ttable (4,437> 2,021). There is regression coefficient between work discipline variable to work effectiveness equal to 0,116 and for regression coefficient from work supervision variable to work effectiveness equal to 0,590 while constant equal to 7,141.Based on the results of the above research can be concluded that the factors of work discipline and supervision of employees is a factor that needs to be considered to create work effectiveness for employees At the Regional Personnel Agency Kabupten Nganjuk. Effectiveness of work for employees At the Regional Personnel Agency Nganjuk included in the category of good but still need to be considered because it is still not optimal.